Association of Fibrinogen Aα Thr312Ala (rs6050) Polymorphism with Venous Thrombosis and Chronic Thromboembolic Pulmonary Hypertension: A Meta-Analysis - Han Cheng MM; Haozhe Yang BM; Yantong Zhang BM; Zhanxu Wei MM; Lei Xia BM; Jing Yang PhD (Clinical and Applied Thrombosis/Hemostasis)
Background Venous thromboembolism (VTE) comprises deep vein thrombosis (DVT) and pulmonary embolism (PE). Chronic thromboembolic pulmonary hypertension (CTEPH) typically arises from acute pulmonary embolism. The pathogenesis of them involves multiple risk factors such as genetic predisposition. However, the findings from these studies are not entirely consistent. This study aims to investigate the association between FGA rs6050 polymorphism and susceptibility to thrombotic diseases. Methods We searched PubMed, OVID, Web of Science, Academic Search Ultimate, CNKI, and Wan Fang database. To assess the strength of associations, we calculated pooled odds ratios (ORs) and 95% confidence intervals (CIs) in different genetic models. Additionally, subgroup analyses, sensitivity analysis, and assessment of publication bias were also carried out. Results A total of 11 studies, including 9 reported results on VTE (3856 individuals [1545 cases]) and 3 on CTEPH (761 participants [350 cases]), revealed a significant association between the rs6050 polymorphism and susceptibility to both VTE and CTEPH. The A allele was consistently linked to an elevated risk of VTE across all genetic models (allele, homozygote, heterozygote, recessive, and dominant model), while it was also associated with an increased risk of CTEPH under all genetic models excluding the recessive model. Furthermore, subgroup analysis among ethnic groups revealed a significant association between rs6050 polymorphisms and VTE in both Caucasians and Asians under all genetic models. In Africans, the association with VTE was only observed for rs6050 polymorphisms in dominant and heterozygous models. Conclusions The FGA rs6050 polymorphism is positively associated with susceptibility to VTE and CTEPH.